Adverse habits and barriers for the adaptation and adoption of reading - Moreno - Mendoza, Edward Fabian; Coronel - Arenas, María Fernanda (Universidad Francisco de Paula Santander, 2018)
Over time, reading has been forged as an indispensable activity for human beings, becoming an indisputable tool for the development of new knowledge and alternative learning in any context, hence its importance within higher education training for the acquisition of skills that generate more integrated people capable of facing any academic and professional process. In line with what has been described, the study seeks to identify the habits that prevent the adaptation and adoption of reading in students of the Business Administration program of the Universidad Francisco de Paula Santander Ocaña, thus knowing the academic, social and economic barriers that hinder reading practices. The methodology of the present investigation is framed within a quantitative approach of descriptive type, using like technique "the survey" applied to a sample of 186 students. The results obtained show that factors such as employment and procrastination are consolidated as adverse habits that inhibit the promotion of reading.